Fabrication of in situ elongated β-Sialon grains bonded to tungsten carbide via two-step spark plasma sintering. Issue 19 (1st October 2021) - Li, Jingmao; Li, Xiaoqiang; Qiu, Hao; Cao, Ting; Qu, Shengguan
Abstract: In order to reduce the difficulty of preparing binder-less cemented carbide and further broaden its application prospects, tungsten carbide toughened by in situ elongated β-Sialon grains was developed via sintering ball-milled WC and α-Si3 N4 powders using Al2 O3 –ZrO2 as a sintering aid and transformation additive. The two-step spark plasma sintering of the mixture at 1650 °C with dwelling at 1500 °C for 10 min was conducted under 30 MPa uniaxial pressure, and the densification behaviors, phase transformations, mechanical properties, and microstructures of the produced composites were investigated. The addition of Al2 O3 –ZrO2 reduced the initial temperature of the densification process by approximately 100 °C and its final temperature by 200 °C (compared with the densification temperatures of pure WC and Si3 N4 materials) and fully transformed α-Si3 N4 to Sialon (Si–Al–O–N) phases. Microstructural characterization data showed that the WC matrix contained homogeneously distributed equiaxed and elongated β-Si5 AlON7 grains. The WC composites containing in situ elongated β-Sialon grains exhibited an optimal hardness of 18.93 ± 0.03 GPa and enhanced fracture toughness of 10.43 ± 0.27 MPa m 1/2 . The toughening mechanism of the β-Sialon phase involved the pull-out of elongated grains and crack bridging.